OPTIMIZATION OF MYSQL DATABASE - Šušter, Ivan; Ranisavljević, Tamara (Journal of process management and new technologies, 2023)
The performance of MySQL, a well-known open-source relational database management system used in a variety of sectors, including e-commerce, finance, and healthcare, can be improved through the use of physical programming and data tuning. While data tuning involves refining the database to increase efficiency, physical programming involves optimizing the physical storage of data. This article gives a general introduction of MySQL and its architecture, looks at the many methods and tools used in physical programming and data tuning, and talks about the advantages of these techniques and how they affect MySQL’s performance.